72.9k views
19 votes
• PQ²+PR²=QR²
• PQ²+QR²=PR²
• PR²- PQ²=QR²
• PR²- QR²=PQ²


• PQ²+PR²=QR² • PQ²+QR²=PR² • PR²- PQ²=QR² • PR²- QR²=PQ² ​-example-1
User Manushi
by
6.0k points

1 Answer

10 votes

Answer:

Option A


{pq}^(2) + {pr}^(2) = {qr}^(2)

Explanation:

This is because here,

PQ is the Height of the right triangle.

QR is the Base of the right triangle.

PR is the Hypotenuse of the right triangle.

So, as according to Pythagoras Theorem,


{base}^(2) + {height}^(2) = {hypotenuse}^(2)

Also,


{pq}^(2) + {qr}^(2) = {pr}^(2)

Not,


{pq}^(2) + {pr}^(2) = {qr}^(2)

Hence, Option A is not correct.

User Realist
by
6.0k points